Commoning in times of finance capitalism. Or: how to think housing. - Gruber, Sabine (TU Wien, 2017)
This paper discusses the commons in the context of contemporary society and its capitalist mainstream. In order to explore the potential of the commons as an alternative to existing structures, I look at housing to compare the governing principles of the commons (co-housing projects) with that of market solutions (investment-based projects). While co-housing projects build enduring structures within certain boundaries, investment-based projects push growth without limits and thus do not foster stable structures. The decision-making processes used in co-housing projects would need to be adapted in order to work at the urban level. Therefore, the paper concludes that commoning is a partial alternative only - while it provides a sustainable lifestyle on a small scale and has potential for transforming the dominant financing system, further integrative steering strategies are required on a medium or large scale.
Keywords: Wohnungspolitik; Wohnungsmarkt; Öffentliche Aufgabe; Wohnungsversorgung; Privatisierung; Öffentliche Güter